Molecular characterisation of Mycobacterium caprae strains isolated in Poland. (10th March 2018) - Krajewska‐Wędzina, Monika; Kozińska, Monika; Orłowska, Blanka; Weiner, Marcin; Szulowski, Krzysztof; Augustynowicz‐Kopeć, Ewa; Anusz, Krzysztof; Smith, Noel H
Abstract : Bovine tuberculosis (bovine TB, bTB) is caused by bovine bacilli: Mycobacterium bovis and M caprae . The studies conducted in Poland, in the National Bovine Tuberculosis Reference Laboratory in the Department of Microbiology of the National Veterinary Research Institute in Pulawy, show that animal tuberculosis in Poland is also caused by M caprae . We here describe the identification and genotypic assessment of 52 isolates of M caprae obtained from Polish cattle and wild animals over the last five years. We show that strains isolated from bison have significant genotypic diversity and are distinct compared with the genotypes of strains isolated from cattle. Similarly, isolates from cattle herds can be highly genotypically variable. Formal designation of the members of the Mycobacterium tuberculosis complex is controversial in Poland; there is a gap in veterinary legislation with regard to bTB and no explicit mention of M caprae causing tuberculosis in animal.